Principals’ Management in Improving Professional Competence of Elementary School Teachers at Jaya Baru Sub-District, Banda Aceh - Marlina, Marlina; Yusrizal, Yusrizal; Usman, Nasir (FKIP Universitas Lampung, 2021)
This research used descriptive qualitative approach. Data collection were conducted through observations, interviews, and documentation. The subjects of this research are principal, vice principal, teacher, and supervisor. The results of this research shows: (1) The program was arranged at the beginning of school year by school development team, including dividing teachers task, arranging annual and semester program, planning to organize a workshop, participating in training, cultivating teachers, creating an innovative learning media, and supervising the class. (2) The program is always implemented according to predetermined plan. The implementation process shown by the improvement of teacher and student discipline, but the principal is still less assertive in disciplining the teacher; (3) The evaluation was done at the end of semester and become the follow-up to determine the following program. The result of evaluation was presented to teacher as individual or group; and (4) The obstacle that occurred are teacher have no basic skill in ICT, not mastering the teaching materials, lack of motivation to read. Keywords: principals’ management, professional competence, elementary school teacher. DOI: 10.23960/jpp.v11.i2.202120